2020
DOI: 10.1103/physrevd.101.074032
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of p -wave hidden-charm exotic mesons in the diquark model

Abstract: We study the fine structure in the spectrum of known and predicted negative-parity hidden-charm exotic meson states, which comprise the lowest P -wave multiplet in the dynamical diquark model. Starting with a form previously shown to successfully describe the S-wave states, we develop a 5parameter Hamiltonian that includes spin-orbit and tensor terms. After discussing the experimental status of the observed J P C = 1 −− states Y with respect to masses and decay modes (classified by eigenvalues of heavy-quark s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 46 publications
(124 reference statements)
0
53
0
Order By: Relevance
“…Despite several experimental observations, the internal constituents of the Yð4220Þ are still unclear. Possible interpretations include hybrids, meson molecules, hadrocharmonium, or tetraquarks, etc., but none of them are conclusive [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite several experimental observations, the internal constituents of the Yð4220Þ are still unclear. Possible interpretations include hybrids, meson molecules, hadrocharmonium, or tetraquarks, etc., but none of them are conclusive [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 96%
“…A partial-wave analysis (PWA) [14] showed that the charged charmoniumlike state Z c ð3900Þ AE , observed in decays to π AE J=ψ in the process e þ e − → π þ π − J=ψ [3,15], and to D ÃD in the process e þ e − → π AE ðD ÃD Þ ∓ [16], has spin-parity J P ¼ 1 þ . Different theoretical models [9][10][11][12][13] consider the Z c ð3900Þ AE to be an unconventional state; in particular, the molecular and tetraquark interpretation [11,13], suggested a strong correlation of the Yð4220Þ to πZ c ð3900Þ. However, further studies are needed to clarify the situation.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of P-wave ccqq 0 states in Ref. [40], the tensor operator is assumed to originate as an analogue to the corresponding operator in nucleon-nucleon interactions arising from pion exchange, and therefore σ couples only to the light quarks within δ andδ, just as for the spin-spin V 0 operator in Eq. (3).…”
Section: Mass Hamiltonianmentioning
confidence: 99%
“…We nevertheless also present an initial fit to the cccc spectrum, using numerical values for the Hamiltonian parameters obtained from the analogous operators in other sectors of exotics to which the model has previously been applied. Specifically, the strength of the spin-spin operator is obtained from a recent fit to ccss candidates [41], and the spin-orbit and tensor strengths are taken from a recent fit to P-wave ccqq 0 candidates [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation